Interfacial Kinetics in Olive Oil-In-Water Nanoemulsions: Relationships Between Rates of Initiation of Lipid Peroxidation, Induction Times and Effective Interfacial Antioxidant Concentrations - Aliaga-Vidal, C; Aliaga-Vidal, C (Academic Press, 2021)
Hypothesis: A detailed quantitative description of the effects of antioxidants in inhibiting lipid peroxidation in oil-in-water emulsions can be achieved by determining the relationships between the rates of initiation of the lipid peroxidation reaction, the length of the induction period preceding the propagation step of the radical oxidation process and the effective antioxidant interfacial concentrations. Experiments: We successfully prepared and characterized a series of olive oil-in-water nanoemulsions and allowed them to spontaneously oxidize. Their oxidative stability was evaluated by carrying out in the presence, and absence, of antioxidants derived from gallic acid, by monitoring the formation of primary oxidation products with time, by determining the corresponding induction periods, and by determining the effective interfacial concentrations of the antioxidants in the intact emulsions. Findings: Results show that both, the length of the induction periods and the antioxidant interfacial concentrations change concomitantly, increasing with the hydrophobicity of the antioxidant up to a maximum at the octyl derivative; longer aliphatic chains decrease their efficiency. The ratio between the interfacial antioxidant concentration and the induction period remains constant independently of the antioxidant, demonstrating that the effective concentrations of antioxidant at the interface control their efficiencies in emulsions. © 2021 The Author(s)